Collaborative Governance Model for Sustainable Village Planning in Kampar District, Riau, Indonesia - Aguswan; Handoko, Rudy; Novaria, Rachmawati (Kirana Publisher (KNPub), 2025)
Sustainable village planning has become a major focus in Indonesia's national development strategy. The concept aims to create rural communities that are resilient, self-reliant, and able to meet the needs of the current generation without compromising future generations' ability to meet their own needs. This study aims to present a governance model for stakeholder collaboration to strengthen sustainable village planning, discussed at the musrenbang forum, starting at the village, sub-district, district/city, and provincial levels. The formulation of village planning involves stakeholders (government, private sector, civil society, universities, and mass media) that can provide input, outcomes, and benefits for sustainable village development planning. This research uses a qualitative, descriptive approach. The analysis of the collaboration model seeks to involve stakeholders in the decision-making process and its implementation. With the Collaboration model for village planning, sustainable village development can be realized. The key to the success of collaboration lies in the commitment of all parties to participate actively.